Multiple Primary Cancer Diagnostic and Theurapetic Challenges: Vaginal Cancer with Cervical Cancer - Sinaga, Rahmanita (Universitas Muhammadiyah Sumatera Utara, 2021)
Multiple primary cancer is diagnosed if multiple cancerous lesions appear in one or more organs in a person either simultaneously or at different times. Differentiating it from metastases, or recurrent cancer is a difficulty and a challenge that must be faced considering that the prognosis of multiple primary cancers is considered to be better if diagnosed correctly. Vaginal cancer is the second primary that should be considered in cervical cancer patients, especially those who have undergone radiation therapy. Treatment of multiple vaginal cancer with cervical cancer is very dependent on the individual considering the limited number of cases is still a limitation in the treatment of these patients, with various therapies in the form of radiation, a combination of surgery with radiation, chemotherapy, and a combination of surgery with chemotherapy.